Resolving the Electroencephalographic Correlates of Rapid Goal-Directed Chunking in the Frontal-Parietal Network - Pang, Jiaoyan; Tang, Xiaochen; Nie, Qi-Yang; Conci, Markus; Sun, Peng; Wang, Haibin; Luo, Junlong; Wang, Jijun; Li, Chunbo; Luo, Jing (Frontiers in Neuroscience, 2019)
Previous study has proved the specific role of prefrontal-parietal network in the rapid goal-directed chunking (RGDC), which could dissociate the prefrontal activity from the working memory demand or encoding difficulty. However, it remains unknown how the prefrontal and parietal cortices collaborate to accomplish RGDC. A novel experiment design using Chinese characters as materials wad conduced with eighteen undergraduate students (9 females, mean age = 22.4 years) while recoding electroencephalogram (EEG). The radical-level chunking, accomplished in a timely stringent way, made a strict contrast with the stroke-level chunking whose cognitive brain processing were far less coherent due to the irregular and unpredictable chunking procedure. Comparing to the stoke-level chunking, RGDC like radical-level chunking showed an early increase of gamma band synchronization over parietal and occipital cortices, followed by enhanced power in the beta-gamma band (25-38 Hz) over frontal areas in the regular versus irregular chunking conditions. We suggest that the posterior rhythmic activities in the gamma band may underlie the processes that are directly associated with perceptual manipulations of chunking, while the subsequent beta-gamma activation over frontal area appears to reflect the reinforcement of the selected rules over alternative options, which would differentiate goal-directed chunking from chunking processes accomplished in a more implicit manner.